The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijms19020448
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis: A Target for Anticancer Therapy

Abstract: Apoptosis, the cell’s natural mechanism for death, is a promising target for anticancer therapy. Both the intrinsic and extrinsic pathways use caspases to carry out apoptosis through the cleavage of hundreds of proteins. In cancer, the apoptotic pathway is typically inhibited through a wide variety of means including overexpression of antiapoptotic proteins and under-expression of proapoptotic proteins. Many of these changes cause intrinsic resistance to the most common anticancer therapy, chemotherapy. Promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
567
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,110 publications
(688 citation statements)
references
References 46 publications
12
567
0
6
Order By: Relevance
“…Natural products constitute an important source of new anticancer molecules, thereby driving a novel direction for the prevention and therapy of cancers [6]. Natural product-derived drugs exert anticancer effects by hampering metastasis and angiogenesis and promoting apoptosis, which are the most important features of human cancers [6,18]. Moreover, drugs derived from natural products are generally endowed with better bioactivities and lower toxicity, and some of them have been combined with conventional therapies to enhance cancer cells' susceptibility [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural products constitute an important source of new anticancer molecules, thereby driving a novel direction for the prevention and therapy of cancers [6]. Natural product-derived drugs exert anticancer effects by hampering metastasis and angiogenesis and promoting apoptosis, which are the most important features of human cancers [6,18]. Moreover, drugs derived from natural products are generally endowed with better bioactivities and lower toxicity, and some of them have been combined with conventional therapies to enhance cancer cells' susceptibility [19].…”
Section: Discussionmentioning
confidence: 99%
“…Different pathways of apoptosis are involved in the induction of cell death, including the mitochondria-mediated and the extrinsic receptor-mediated pathways, within which caspase-9 and 8 play essential roles, respectively. These, in turn, activate caspase-3 and fragmentation of DNA [17,18]. To investigate the involvement of these caspases, AC-treated HT-29 cell lysates were used to perform fluorescence assays with specific caspase-3, 8 and 9 substrates.…”
Section: Ac-induced Changes In Caspase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study we also showed that miR-494 inhibitor prevented apoptosis and augmented cell viability by rescuing the cells from the effects of cellular endogenous miR-494, pointing out that the reduction of miR-494 might lead to improved cell survival. Apoptosis plays a crucial role in cancer management and therefore is considered as a protective mechanism against tumor progression and metastasis (Pfeffer and Singh, 2018[33]; Hickman, 1992[20]). Moreover, the anticancer activity of most of the chemotherapeutic drugs relies on inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among vanadium compounds V 2 O 5 is highly toxic (Naso et al, 2016) but the oxidovanadium/luteolin complex (Roy & Chakraborty, 2018) or vanadium/luteolin complex (Pfeffer & Singh, 2018) are also inducers of apoptosis via activation of p53, Bax and caspase-3, key proteins involved in the intrinsic pathway (Weigel et al, 2014). Our results with NaVO 3 showed that none of the intrinsic or extrinsic molecules was significantly modified, as the final pathways products, caspase-3 and/or caspase-7, remained unaltered independently of the treatment time.…”
Section: Discussionmentioning
confidence: 99%